The Relation of Enuresis and Irritable Bowel Syndrome with Premature Ejaculation: A Preliminary Report - Barghi, Mohammad Reza (Urology Journal, 2009)
Introduction: In this retrospective study, we reviewed the outpatient data of patients with premature ejaculation to investigate the association of that disorder with irritable bowel syndrome and a positive history of enuresis. Materials and Methods: All patients with premature ejaculation who had presented to the author's office from March 2002 to June 2003 were selected. Their medical records were reviewed, and data including symptoms of irritable bowel syndrome, history of enuresis, and psychologic disorders were collected. The results of our analysis were compared with the worldwide reported prevalence of enuresis and irritable bowel syndrome in the male general population. Results: Forty-one consecutive patients were asked whether they had ever experienced irritable bowel syndrome, enuresis, psychologic problems, and/or the feeling of tickling or sexual pleasure at ejaculation. Of those 41 patients, 18 reported the symptoms of irritable bowel syndrome (43.9% versus 10% in the general population; P < .001). A reliable answer about the history of enuresis was obtained from 35 patients, 14 of which had experienced that disorder (40% versus 10% in the general population; P < .001). Of those 35 patients, 6 (17.4%) had experienced both irritable bowel syndrome and enuresis. Twenty-two of 37 patients (59.5%) reported psychologic problems including stress, agitation, and obsession-compulsive disorder. Conclusion: The results of this study suggest the association of premature ejaculation with irritable bowel syndrome and enuresis, which in turn may indicate that those disorders share a common neurologic pathophysiology. A special attention of the physicians to the symptoms of these diseases together may be of great help for the patients.